Students’ Perspective On Committing Plagiarism In Academic Writing Class - Suddin M. Saleh Djumadil; Fitriningsih Pratiwi Mahmud; Ahmad Rifani Talaohu (South Sulawesi Education Development (SSED), 2024)
Plagiarism is a pervasive and serious ethical issue that involves the unauthorized use or appropriation of someone else's ideas, words, or creative work without proper acknowledgment or permission. It is an act of intellectual dishonesty that undermines the principles of academic and professional integrity. The term encompasses various forms of misrepresentation, including copying and pasting text, paraphrasing without proper citation, and presenting someone else's work as one's own. Plagiarism can be a common issue in educational settings, and various factors contribute to its prevalence. Therefore, it is important to understand these factors, especially from students’ point of view in order to help teachers take proactive measures toward plagiarism effectively. Based on this case, the purpose of this study is to examine undergraduate students’ perspective on potential causes of plagiarism in academic writing through qualitative data collection methods. The data will be collected from students in the English Department, Faculty of Cultural Science, Universitas Khairun (Unkhair) through a series of interviews. Students selected for the interview are those who have previously taken a writing test in which their results contained plagiarism. The analysis includes several reasons on why students tend to plagiarize. These reasons are thus summarized in a form of ‘theme’, which is why; thematic analysis approach is used for analyzing the data. The main themes that emerge from the aforementioned problem are: poor awareness of plagiarism; poor academic writing skills; laziness behaviors; deadlines and pressures; teaching issues; lack of integrity, and; grade over knowledge. The study results show that the causes of plagiarism are varied, and the description provided by students are able to help developing a strategy against plagiarism so that students will be more cautious and prioritize their own original work and academic honesty. Keywords: English Department, Plagiarism, Reasons, Students’ Perspective, Theme